Hesperidin increase cytotoxic effect of doxorubicin in MCF-7 cells - Adam Hermawan (Indonesian Journal of Pharmacy, 2010)
Hesperidin, a flavonoid, shows strong cytotoxic effect in several cancer cell lines. The aim of this research was to investigate cytotoxic activities of hesperidin alone and in combination with doxorubicin. Cell viability assay of hesperidin, doxorubicin, and combination treatments were carried out by using MTT assay. Apoptosis assay was done using double staining method using Ethidium Bromide-Acridine Orange. Hesperidin did not show cytotoxic effect          but doxorubicin showed cytotoxic effect with IC50 467 nM. Hesperidin (5, 50 and  100 µM) increased cytotoxic effect of doxorubicin compared with doxorubicin alone. The strongest cytotoxic activity was showed by the combination of 200 nM doxorubicin and 100 µM hesperidin. Combination treatment of doxorubicin 200 nM and hesperidin 100 µM induced apoptosis in MCF-7 cells. Hesperidin is potentially to be developed as co-chemotherapeutic agent for breast cancer, while molecular mechanism need to be explored.  Key words: Hesperidin, doxorubicin, synergism, MCF-7, apoptosis